EDITORIAL - Sayyid M. Syeed (International Institute of Islamic Thought, 1990)
In this issue we have included the opening address of Taha Jabir Al- ‘Alwani which was delivered at the First AMSS History Conference with the theme of “Strategies for an Islamic Perspective on History and Historical Writing,” that was held on Dhu al Qidah 1-2, 1411/May 26-27, 1990. Al- ‘Alwani states that the collapse of Marxism all Over the world is a logical conclusion of the philosophies which circulated in the West with a stamp of undeserved academic authority and universality. Western thought, he says, will explain the fall of Marxism by trying to revive philosophies removed from Marxism and condemning Marxism as being opposed to human nature, antithetical to freedom and democracy, and opposed to the natural flow of history. But the alternatives to be projected will not be essentially any different. Therefore, Al- ‘Alwani  warns, the glee we witness in the West at the collapse of Marxism will be short-lived because before too long the shortcomings of Westem thought will become more apparent. What is needed for removing the suffering of mankind is a comprehensive alternate philosophy that presents a realistic and satisfactory interpmtion of history, an overall conception of life, mankind, and the universe. Al-‘Alwani argues that the Qur’anic interpretation of time, life, the universe, mankind, history, and good and evil provides contemporary humanity with a philosophical and civilizational alternative that is capable of leading mankind out of the present crisis. It is in this context that the contributions of MISS become relevant. Our writers are engaged in providing a critique of the Wstern disciplines and then highlighting the features oftheir Islamized versions. Abdul Rashid Moten attempts a contrast between the Western mode of political inquiry and the Islamic alternative. This underscores the fact that the methodology and epistemology of Western political science is built mund the seemingly limitless power of natural sciences. Moten exposes the subjective and ideological nature of political science in its own epistemic landscape from real life situations. He concludes that the instrumentalist conception of political community and the final packaging of knowledge are all colored with the social, cultural, and historical experience of Western Christianity, which is also, paradoxically, materialistic and secular to the core. By identifying reason and revelation as the twin sources of knowledge, Islamic political thought is associated with such Qur‘anic concepts as Tawhid, Khilafah, ‘Ibadah, 'Adl, and the like ...